DIVINE VOLUNTARISM AND COMPLEX ETHICAL SYSTEMS: An introduction - Costa, Daniel; Assumpção, Gabriel (Sapere Aude, 2025)
This paper explores the relationship between theology and ethics from the perspective of divine command theory, emphasizing the tensions and challenges it poses to complex ethical systems. Ethics is understood here as a dynamic system of value construction and negotiation, whose legitimacy depends on intersubjective processes of validation and recognition. The paper examines the epistemological and normative viability of incorporating moral precepts grounded in divine commands, particularly in light of the plurality of normative criteria and the inherent subjectivity of religious experience. We argue that, although the theological grounding of moral norms may be coherent within certain belief systems, its application in pluralistic social contexts requires integrative mechanisms that preserve the cohesion and stability of the ethical system as such. We therefore contend that the admissibility of divine commands as a source of moral authority must be mediated by criteria that safeguard the integrity of the normative system, allowing for the validity of individual experiences only within boundaries that maintain that integrity.